Die Religionspädagogik und das Grundgesetz. Sondierungen zu einem dynamisch-geistreichen Wechselverhältnis - Schlag, Thomas (Zeitschrift für Pädagogik und Theologie, 2019)
By taking recourse to the conditions surrounding the origin of the specific content of Germany’s federal Constitution which is relevant for matters of religion, the essential constitutional foundations of the responsibility to offer religious education also come into view. At the same time, such an historical orientation allows to define more closely, in accordance with the “spirit” of the Constitution, what the current challenges for religious education are and to do it in such a way as to inform current and future discussions of it. The stipulations of the Constitution and of fundamental rights which are relevant for the topic of religion are, in the truest sense of the term, not carved in stone. They require, rather, an ongoing transformation which is appropriate to the current situation and which results in concrete processes of education which are oriented towards democracy and human rights.